1992 World Economic and Financial Surveys : Private Market Financing for Developing Countries 1992. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1992)
This paper reviews recent developments in private market financing for developing countries. Bank creditors themselves have been more amenable to restructuring in an environment where secondary market discounts on bank claims were falling significantly below the level of bank provisioning. This has allowed banks to realize substantial book profits by participating in debt operations. Debt conversions have also played a substantial role in reducing commercial bank debt. The pace of such conversions, however, has slowed over the past year in response to lower secondary market discounts on external debt and to a drop in privatization-related conversions. The re-entry to international capital markets by certain middle-income countries that had experienced debt-servicing difficulties gathered momentum over the past year. Total bond issues in international markets by the main re-entrants accounted for over half of issues by developing countries in this period. In contrast to the experience in securities markets, new bank lending to market re-entrants has remained limited and is confined mainly to short-term trade lines or project financing.